Intranasal Dexmedetomidine-Esketamine Combination Premedication versus Monotherapy for Reducing Emergence Delirium and Postoperative Behavioral Changes in Pediatric Tonsillectomy and/or Adenoidectomy: A Randomized Controlled Trial - Liao Y; Xie S; Zhuo Y; Chen S; Luo Y; Wei Y; Yao Y (Dove Medical Press, 2024)
Yanling Liao,1,* Siyu Xie,2,* Yifen Zhuo,3,* Sisi Chen,1 Yuxin Luo,1 Ying Wei,4 Yusheng Yao1 1Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, Fuzhou, People's Republic of China; 2Department of Anesthesiology, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, People's Republic of China; 3Department of Anesthesiology, Xiamen Haicang Hospital, Xiamen, People's Republic of China; 4Department of Anesthesiology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Ying Wei, Department of Anesthesiology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, 18 Daoshan Road, Fuzhou, 350025, People's Republic of China, Email whm444@fjmu.edu.cn Yusheng Yao, Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital, 134 Dongjie Street, Fuzhou, 350001, People's Republic of China, Email fjslyys@126.comPurpose: Emergence delirium and postoperative negative behavioral changes (PNBC) are common complications in pediatric anesthesia. This study evaluated whether intranasal premedication combining dexmedetomidine and esketamine more effectively reduces these complications compared to either drug alone in children undergoing tonsillectomy and/or adenoidectomy with sevoflurane anesthesia.Patients and Methods: This randomized, double-blind trial involved 198 children aged 2− 5 years undergoing tonsillectomy and/or adenoidectomy. Participants received intranasal premedication with either dexmedetomidine (2 μg/kg), esketamine (1 mg/kg), or their combination (dexmedetomidine 1 μg/kg plus esketamine 0.5 mg/kg). The primary outcome was the incidence of emergence delirium, defined as a Pediatric Anesthesia Emergence Delirium (PAED) scale score ≥ 10. Secondary outcomes included the incidence of PNBC, sedation depth, easiness of separation from parents, acceptance of the mask for induction, emergence time, postoperative pain score, parental satisfaction, and adverse events.Results: The combination premedication significantly reduced emergence delirium incidence (9.4%) compared to esketamine alone (38.1%; relative risk [RR] 0.25, 95% confidence interval [CI] 0.11- 0.57, p < 0.001), but not compared to dexmedetomidine alone (17.2%; RR 0.55, 95% CI 0.21- 1.39, p = 0.193). PNBC incidence at day 7 was lower with the combination (28.1%) versus dexmedetomidine (48.4%; RR 0.58, 95% CI 0.36- 0.93, p = 0.018), but not significantly different from esketamine alone (20.6%; RR 1.38, 95% CI 0.74- 2.58, p = 0.326). The combination also provided significantly superior sedation, improved ease of separation from parents, better acceptance of the mask for induction, shorter emergence time, and higher parental satisfaction than both monotherapies.Conclusion: In children undergoing tonsillectomy and/or adenoidectomy with sevoflurane anesthesia, intranasal dexmedetomidine-esketamine premedication more effectively reduces emergence delirium compared to esketamine alone and PNBC compared to dexmedetomidine alone. This combination also improves sedation, shortens emergence times, and enhances parental satisfaction compared to monotherapy without significant adverse effects.Trial Registration: The Chinese Clinical Trial Registry, ChiCTR2300076709. Keywords: adenoidectomy, dexmedetomidine, emergence delirium, esketamine, intranasal administration, pediatric anesthesia, postoperative complications, tonsillectomy